2015
DOI: 10.1039/c4cp04502e
|View full text |Cite
|
Sign up to set email alerts
|

Topological states modulation of Bi and Sb thin films by atomic adsorption

Abstract: Based on first-principles calculations, we systematically investigated the topological surface states of Bi and Sb thin films of 1-5 bilayers in (111) orientation without and with H(F) adsorption, respectively. We find that compared with clean Bi and Sb films, a huge band gap advantageous to observe the quantum spin Hall effect can be opened in chemically decorated bilayer Bi and Sb films, and the quantum phase transition from trivial (non-trivial) to non-trivial (trivial) phase is induced for a three bilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
(33 reference statements)
2
16
0
Order By: Relevance
“…However, the origin of nontrivial topology in halogenated arsenene results from the massive Dirac point and there is no band inversion, where the mechanism is similar to that in functionlized Bi/Sb films12131447. Around Fermi level, there are massive Dirac cones at the K point and nearly flat bands (the second band below the Fermi level) in the band structures of halogenated arsenene.…”
Section: Resultsmentioning
confidence: 95%
“…However, the origin of nontrivial topology in halogenated arsenene results from the massive Dirac point and there is no band inversion, where the mechanism is similar to that in functionlized Bi/Sb films12131447. Around Fermi level, there are massive Dirac cones at the K point and nearly flat bands (the second band below the Fermi level) in the band structures of halogenated arsenene.…”
Section: Resultsmentioning
confidence: 95%
“…Compared with pure arsenene, the p z orbital components are removed from the low-energy spectrum in the decorated arsenene with dangling bonds saturated. The role of SOC in AsCH 3 and AsOH films is to open up energy gap at the K point as in the case of surface decorated Bi and Sb [39,41], suggesting that the AsCH 3 and AsOH films may be 2D TIs.…”
Section: Resultsmentioning
confidence: 97%
“…Hence effective and feasible method should be proposed for arsenene. Many reports have shown that chemical decoration is helpful to modulate the structural, electronic and topological properties of 2D materials, such as chemically modified germanene [38], stanene [22], and Bi film [39][40][41][42]. It has been recently shown to be also effective in arsenene to induce nontrivial phase with full hydrogenation and halogenation [32].…”
Section: Resultsmentioning
confidence: 99%
“…The electronic band at the surface differs from that in the bulk mostly by a pronounced narrowing of the Fe-derived bands resulting from the reduced coordination of the Fe atoms. That does not follow the traditional rule of “the band gap of bulk is smaller than that of film” [40]. The Fe-surface moment is 3.99 (4.00) μ B in 1 × 1 × 1 (1 ×1 × 3) thin film.…”
Section: Resultsmentioning
confidence: 97%